Anestesia para separação de gêmeos isquiópagos no período neonatal. Relato de caso - Pinheiro Módolo, Norma Sueli [UNESP]; Amorim, Rosa Beatriz [UNESP]; Machado Castiglia, Yara Marcondes [UNESP]; Dias, Simone A. [UNESP]; Guasti, Valter M. [UNESP] (My University, 2002)
Background and Objectives - The separation of conjoined twins has always raised considerable interest because of surgical and anesthetic complexity, pathology rarity and few survival chances. The goal of this description was to contribute to existing literature by reporting the challenges faced by our team during an anesthetic-surgical procedure for ischiopagus twins separation. Case Report - Term conjoined twins, born from Cesarean section, weighing together 5100 g, who were classified as ischiopagus tetrapus. Two anesthetic-surgical teams were present and the anesthetic procedure was programmed using two units of each device: anesthesia machine, cardioscope, capnograph, pulse oximetry, electric thermometer and esophageal stethoscope. Halothane and fentanyl were used for anesthesia induction, with the twins in the lateral position and 45° head rotation to allow tracheal intubation. Ventilation was manually controlled using Rees-Baraka systems. Anesthesia was also maintained with halothane, fentanyl and oxygen. Double abdominal organs were found during surgery, except for the single colon. Bladders and ischia were joined. At surgery completion, twins had stable vital signs. They remained in Neonatal Intensive Care Unit for four weeks and were discharged in good general conditions. Conclusions - The importance of the team's meshing of gears, multidisciplinary retrospective studies, adequate and careful monitoring and good clinical observation is emphasized. All those factors contributed for twins' good evolution.
Anesthetic management for neonatal conjoined twins separation. Case report
Keywords: Anesthesia, Pediatric; Surgery, Pediatric: separation of isquiopagus twins